Procedimentos ambientais e sua utilização no desenvolvimento e implementação de um sistema de gestão ambiental - Brandão, Fábio de Souza (2014)
The growth of the world population and its productivity throughout the twentieth century brougth as a consequence the scarcity of natural resources, which threaten the future of humanity. The advances in technology, the access to information and the increase of competitiveness, showed to the population the importance of the planets environmental sustainability. Worldwide society, financial agencies, insurers and governments started pressuring companies to apply actions to preserve the environment. Being so, various movements, events, conferences and agreements were displyed in support of the environmental preservation related to management, highlighting the need tof establish goals and to include environmental issues in a responsible environmental management. Thus, this dissertation aims to study environmental procedures and tools that contemporary organizations have access today and to show how they support the development and the implementation of an Environmental Management System - EMS following the ISO 14001. Organizations that dont implement this kind of management use the argument of the expenditure of such a system. Thus, the purpose of this work is to provide evidence of the benefits associated with a business management aiming the environmental preservation, throuh the study of environmental tools in use today as Environmental Audist, Environmental Licensing Process, Environmental Impact Assessments - EIA, Reports of Impacts on the Environment - RIMA, GRI, Seals and Certifications. These tools had their origins, development, contents, natures, rules and associated legal aspects studied with the purpose of comparing them with the characteristics of an EMS. The studies developed allowed to conclude that the contents of the EMS in little differs from the contents of some of the studied tools. The methodology used in this dissertation was descriptive, explanatory, applied, aiming to present the characteristics of the available environmental tools that facilitate the development and implementation of an EMS, using a bibliographic and documentary research: books, articles, journals, thesis, websites on the topics of Sustainability, Environment, Environmental Management Systems and tools associated with SGA, as well as some laws, decrees and regulations and official government sources.